Benefits of Polyamide Nanofibrous Materials: Antibacterial Activity and Retention Ability for Staphylococcus Aureus - Lencova, Simona; Zdenkova, Kamila; Jencova, Vera; Demnerova, Katerina; Zemanova, Klara; Kolackova, Radka; Hozdova, Kristyna; Stiborova, Hana (Nanomaterials (Basel, Switzerland), 2021)
Although nanomaterials are used in many fields, little is known about the fundamental interactions between nanomaterials and microorganisms. To test antimicrobial properties and retention ability, 13 electrospun polyamide (PA) nanomaterials with different morphology and functionalization with various concentrations of AgNO3 and chlorhexidine (CHX) were analyzed. Staphylococcus aureus CCM 4516 was used to verify the designed nanomaterials' inhibition and permeability assays. All functionalized PAs suppressed bacterial growth, and the most effective antimicrobial nanomaterial was evaluated to be PA 12% with 4.0 wt% CHX (inhibition zones: 2.9 ± 0.2 mm; log10 suppression: 8.9 ± 0.0; inhibitory rate: 100.0%). Furthermore, the long-term stability of all functionalized PAs was tested. These nanomaterials can be stored at least nine months after their preparation without losing their antibacterial effect. A filtration apparatus was constructed for testing the retention of PAs. All of the PAs effectively retained the filtered bacteria with log10 removal of 3.3-6.8 and a retention rate of 96.7-100.0%. Surface density significantly influenced the retention efficiency of PAs (p ≤ 0.01), while the effect of fiber diameter was not confirmed (p ≥ 0.05). Due to their stability, retention, and antimicrobial properties, they can serve as a model for medical or filtration applications.
Keywords: nanofiber; polyamide; long-term stability; antimicrobial activity; filtration apparatus; permeability; Staphylococcus aureus